PENGARUH PENDAPATAN ORANGTUA DAN GAYA HIDUP TERHADAP PERILAKU KONSUMSI MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Melli Yanti Natasya; Nuraini Asriati; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The purpose of this study is to determine: How much influence parents' income and lifestyle on consumption behavior of students of Economics Education FKIP Untan. This study uses a quantitative approach by using the type of correlational research. The population of this research is Regular Economics Education Students FKIP Untan class 2017, 2018, and 2019. The sample in this study amounted to 81 students using the Probability Sampling technique. Data collection techniques in this study used questionnaires and documentation. The results showed that: parental income and lifestyle had a simultaneous significant effect on the consumption behavior of Economic Education Students FKIP Untan by 23.9% and the remaining 76.1% was influenced by other variables not examined, and also proven by Fcount (12,258) Ftable (3.11) and the significance level is (0.000 < 0.05). The conclusion is that there is an effect of parental income and lifestyle on the consumption behavior of Economic Education Students FKIP Untan by 23.9% and the remaining 76.1% is influenced by other variables not examined.